Community-Based Non-Formal Education to Prevent Juvenile Delinquency: A Case Study of Rumah Pintar Kokoda in West Papua - Maemonah, Maemonah; Hernawati, Sari; Basori, Ruchman; Sijabat, Jenro P. (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2024)
Purpose – This study explores the implementation and impact of the Rumah Pintar (Smart House) initiative in Kokoda, West Papua, which aims to address juvenile delinquency through community-based non-formal education. The research is significant as it responds to urgent social concerns by offering a culturally grounded educational strategy that enhances adolescent literacy, moral awareness, and social behavior. Design/methods/approach – This study employs a qualitative approach using an intrinsic case study method to explore the effectiveness of the Rumah Pintar in Kokoda Village in mitigating juvenile delinquency through non-formal education. Data were collected through participatory observation, semi-structured interviews, and document analysis, with participants selected purposively. Thematic analysis was employed, and data validity was ensured through triangulation and member checking. Findings – The findings reveal that strategic planning by community leaders—focused on addressing alcohol consumption, poverty, and lack of religious knowledge—significantly contributes to reducing delinquent behavior. Despite facing operational challenges and the absence of a formal evaluation system, the initiative has succeeded in lowering school dropout rates and promoting positive behavior through religious education and practical job training. Research implications – This study highlights the need for additional support and resources to improve educational infrastructure. Future research should focus on developing structured evaluation mechanisms and exploring further community-based strategies for youth development, emphasizing the critical role of education and moral guidance.